2020
DOI: 10.3390/molecules25184312
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure–Activity Relationships of Thiazole Analogs as Anticholinesterase Agents for Alzheimer’s Disease

Abstract: Dementia is a neurological condition commonly correlated with Alzheimer’s disease (AD), and it is seen with many other central nervous system (CNS) disorders. The restricted number of medications is not appropriate to offer enough relief to enhance the quality of life of patients suffering from this symptom; thus, all therapeutic choices should be carefully assessed. In this study, new thiazolylhydrazone derivatives (2a–2l) were designed and synthesized based on the cholinergic hypothesis. Their chemical struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…To observe the BBB permeability of the active compounds 3i and 3j , the parallel artificial membrane permeability assay (PAMPA) was performed as previously described [ 21 ]. Briefly, the solutions of each compound were prepared in dimethyl sulfoxide (DMSO) at 10 mM and then diluted with PBS (Phosphate-Buffered Saline; pH = 7.4) to obtain the donor drug solution with the nominal final concentration of 100 μM (297 μL of buffer + 3 μL of DMSO drug solution).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To observe the BBB permeability of the active compounds 3i and 3j , the parallel artificial membrane permeability assay (PAMPA) was performed as previously described [ 21 ]. Briefly, the solutions of each compound were prepared in dimethyl sulfoxide (DMSO) at 10 mM and then diluted with PBS (Phosphate-Buffered Saline; pH = 7.4) to obtain the donor drug solution with the nominal final concentration of 100 μM (297 μL of buffer + 3 μL of DMSO drug solution).…”
Section: Methodsmentioning
confidence: 99%
“…Compounds with dual binding affinity to both active binding sites of the AChE enzyme, such as donepezil, have an excellent AChE inhibition profile [ 19 , 20 ]. In continuation of our previous research [ 21 ], in this work, we designed and synthesized a series of donepezil-based molecules with an evaluation of their AChE inhibitor activity in comparison to donepezil, as shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the synthesized compound, 123 was found to be the most active agent in the series with an IC 50 value of 0.028 ± 0.001 µM, which indicated an inhibition profile similar to the reference drug, donepezil. The highly active compound 123 might exhibit anticholinesterase activity due to the presence of hydroxyl and methoxy moieties at the third and fourth positions of the phenyl ring [158].…”
Section: Thiazoles As Anti-alzheimer Agentsmentioning
confidence: 99%
“…15 Studies have shown that rivastigmine's dual inhibitory activity elicits a better patient response in terms of stabilization of diseases, improvement in cognitive function, and reduction in the burden of concomitant psychoactive treatment. 16 Although many researchers have focused on finding new small molecules structurally derived from FDA-approved drugs such as tacrine and donepezil, 17 some have discovered other five-membered heteroaryls such as thiazoles 18 and 1,3,4oxadiazoles 19 as multitargeted hybrids for AD.…”
Section: Introductionmentioning
confidence: 99%